Digitalisasi Pemasaran melalui Sosial Media Marketing pada UMKM di Wilayah Banjarmasin - Edy Mahfudz; Ridha Septina Arini; Periyadi Periyadi; Hairul Hairul; Sanusi Sanusi; Abdurrahman Abdurrahman; M. Gunawan Perdana (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of regional economies, including in the city of Banjarmasin, as they play a crucial role in job creation and income generation for local communities. However, many MSMEs continue to face challenges in the marketing aspect, particularly due to their reliance on conventional marketing methods that have limited reach and require relatively high costs. In response to these issues, this community service program aims to promote the digitalization of MSME marketing methods in Banjarmasin through intensive training and mentoring in the utilization of social media marketing. The implementation methods include an initial needs assessment survey to identify partners’ levels of understanding, workshops on digital marketing strategies, and hands-on mentoring for direct implementation on social media platforms such as Instagram and Facebook. The results of the program indicate a significant improvement in MSME actors’ knowledge and skills, particularly in managing business accounts, developing content strategies, and creating visually appealing content that aligns with target market characteristics. Furthermore, MSME partners were able to expand their market reach more effectively and efficiently, which is expected to enhance business competitiveness and sustainability in the digital era.